A modelagem conceitual de publicações seriadas em ambiente Linked Data na perspectiva dos modelos IFLA LRM e PRESSoo - Oliveira, Rhuan Henrique Alves de (2024)
The PRESSoo and IFLA Library Reference Model (IFLA LRM) models emerge in the rise of the digital environment context, where cataloging practice is increasingly reflected in the Semantic Web and Linked Data scenario. These models propose new approaches and solutions for describing and sharing serial publication data. Therefore, this research aims to investigate and present the modeling of serials using the PRESSoo and IFLA LRM models, starting from the contextualization of the description of these resources in a Linked Data environment. To this end, a Systematic Literature Review (SLR) was carried out, seeking to identify how the models are being discussed in the scientific literature, presenting their approaches, using as reference the documents of the respective models published by the International Federation of Library Associations (IFLA). The applied study sought to integrate the exhaustive and granular modeling of serial publications by PRESSoo, which constitutes a specific model within the scope of continuous resources, and IFLA LRM, which constitutes a general model with a high level of abstraction of the bibliographic universe, from the extension mechanisms of this model. It was identified that PRESSoo has a granular and exhaustive modeling of serial publications with classes and properties that cover the entire scope of descriptive elements of these resources, while IFLA LRM, as a model that treats the bibliographic universe in general guidelines , has a modeling with greater emphasis on the entity structure. It is concluded that both models provide a satisfactory and elementary conceptual structure for the description of serial publications in a Linked Data environment, as well as solutions to the complex problems of these resources and a complete shared understanding of this domain, thus constituting as solutions for mapping and interoperability of other vocabularies.